Positive and negative mood in men with advanced prostate cancer undergoing androgen deprivation therapy: considering the role of social support and stress. Issue 8 (23rd September 2014) - Benedict, Catherine; Dahn, Jason R.; Antoni, Michael H.; Traeger, Lara; Kava, Bruce; Bustillo, Natalie; Zhou, Eric S.; Penedo, Frank J.
Abstract Advanced prostate cancer patients often undergo androgen deprivation therapy (ADT). Advanced disease and adverse ADT side effects are often debilitating and negatively impact mood. Social support has been shown to mitigate detrimental effects of stress on mood. Objective This study sought to characterize positive and negative mood in this select patient population and determine whether social support moderated relations between stress and mood. Methods Participants (N = 80) completed the Interpersonal Support Evaluation List, Perceived Stress Scale, and Derogatis Affect Balance Scale at a single time point. Hierarchical regression models evaluated relations among social support, stress, and mood controlling for relevant covariates. Standard moderation analyses were performed. Results Participants reported higher levels of negative and positive mood compared with published means of localized prostate cancer patients. Overall, mood was more positive than negative. Stress levels were comparable to cancer populations with recurrent disease. Moderated regression analyses showed that social support partially buffered the effects of stress on positive mood; men with high stress and low support reported the lowest levels of positive mood. The model with negative mood as the dependent measure did not support moderation; that is, the relationship between stress and negative mood did not differ by level of social support. Conclusion Among individuals living with advanced prostate cancer, social support may be an important factor that sustains positive mood in the presence of stress. Future work should examine the extent to which social support prospectively impacts health‐related quality of life by promoting positive mood. Limitations include cross‐sectional design, which precludes causal inferences. Copyright © 2014 John Wiley & Sons, Ltd.